Movement Framing and Discursive Opportunity Structures: The Political Successes of the U.S. Women's Jury Movements - McCammon, Holly J.; Muse, Courtney Sanders; Newman, Harmony D.; Terrell, Teresa M. (American Sociological Review, 2007)
Collective actors typically attempt to bring about a change in law or policy by employing discursive tactics designed to convince key political decision-makers to alter policy, yet few systematic studies of the effects of social movement framing on political outcomes exist. We theorize that the cultural context in which framing takes place moderates the success of movement framing in winning changes in policy. We examine the efforts of organized women, during roughly the first half of the twentieth century, to convince lawmakers to broaden jury laws to give women the opportunity to sit on juries. To examine the combined effect of framing and the discursive opportunities provided by hegemonic legal principles, traditional gender beliefs, gendered political opportunities, opposition framing, and wartime, we use logistic regression. The findings provide substantial evidence that framing's influence is moderated by discursive elements in the broader context. Our results suggest that investigations of how citizen groups influence law and policy must take into account framing's important role and the ways in which the cultural context conditions framing's influence.